Effectiveness of Indirect and Direct Laryngoscopes in Pediatric Patients: A Systematic Review and Network Meta-Analysis - Hiroshi Hoshijima; Takahiro Mihara; Shinichi Kokubu; Sakura Takeda; Toshiya Shiga; Kentaro Mizuta (MDPI AG, 2022)
This research aimed to produce a coherent ranking of the effectiveness of intubation devices in pediatric patients using network meta-analysis (NMA). We searched the electric databases for prospective randomized studies that compared different tracheal intubation devices in pediatric patients. The primary outcome was intubation failure at the first attempt. Secondary outcomes were glottic visualization and intubation time. The statistical analysis performed used DerSimonian and Laird random-effects models. Frequentist network meta-analysis was conducted, and network plots and network league tables were produced. Subgroup analysis was performed after excluding rigid-fiberscope-type indirect laryngoscopes. Thirty-four trials comparing 13 devices were included. Most laryngoscopes had the same intubation failure rate as the Macintosh reference device. Only the Truview PCD™ had a significantly higher intubation failure rate than the Macintosh (odds ratio 4.78, 95% confidence interval 1.11-20.6) The highest-ranking laryngoscope was the Airtaq™ (P score, 0.90), and the AirwayScope™, McGrath™, and Truview EVO2™ ranked higher than the Macintosh. The Bullard™ had the lowest ranking (P score, 0.08). All laryngoscopes had the same level of glottic visualization as the Macintosh and only the C-MAC™ had a significantly shorter intubation time. Intubation time was significantly longer when using the GlideScope™, Storz DCI™, Truview PCD™, or Bullard™ compared with the Macintosh. P score and ranking of devices in the subgroup analyses were similar to those in the main analysis. We applied NMA to create a consistent ranking of the effectiveness of intubation devices in pediatric patients. The findings of NMA suggest that there is presently no laryngoscope superior to the Macintosh laryngoscope in terms of tracheal intubation failure rate and glottic visualization in pediatric patients.